Chemical constituents of ripe Momordica charantia by Gas Chromatography Mass Spectrometry (GCMS) - Diah Miftahul Aini; Baiq Desy Ratnasari; Zul Hendry (Yayasan Literasi Sains Indonesia, 2022)
Momordica charantia, commonly called bitter melon, is a plant belonging to Cucurbitaceae family known for centuries for its nutritional properties. This plant have been used as folklore medicine for the management of hypertensions, cold, cough, and diabetes. The aim of the present study was to characterize the chemical constituents of ripe M. charantia from Lombok, Indonesia by Gas Chromatography Mass Spectrometry (GCMS). The method that used is maseration with ethanol as solvent. The ethanol extract of ripe M. charantia was characterized by gas chromatography-flame ionization detection and gas chromatography coupled with mass spectrometry analyses. The chemical constituent of ripe M. charantia that followed by GCMS were 2,4-Pentanediol (23,61 %), Eucalyptol (1,8-Cineole) (20,41 %), Trans (Beta)-Caryopyllene (10,07 %), 3-Decyn-2-ol (9.54 %), Epiglobulol (7.82 %), Methyleugenol (7.15%), Beta-Selinene (5.80 %), Alpha-Selinene (5.43 %), and Alpha-Humulene (5.29 %). This is the first report on chemical screening of ethanol extract of ripe M. charantia and GC-MS analysis shows the presence of compounds which have medicinal properties.